Workshop Pengembangan Media Pembelajaran Interaktif Berbasis Artificial Intelligence (AI) Bagi Guru di SMA Negeri 4 Kota Gorontalo - Sitti Roskiana Mas; Arifin Arifin; Arifin Suking; Cinta Labaso; Putri Nabila Sumito (Universitas Negeri Gorontalo, 2026)
The rapid development of information and communication technology requires teachers to possess competencies in utilizing interactive digital learning media to support 21st-century learning. However, preliminary observations at State Senior High School 4 Gorontalo revealed that some teachers still faced limitations in using information technology (IT)-based learning media and Artificial Intelligence (AI) applications in teaching practices. This community service program aimed to enhance teachers’ competencies in designing and implementing interactive IT-based learning media. The activity was conducted through a workshop using a participatory approach consisting of preparation, material presentation, hands-on practice, evaluation, and follow-up stages. The participants were 36 teachers from various subject areas at State Senior High School 4 Gorontalo. The results indicated improvements in teachers’ understanding and practical skills in developing digital learning media, including interactive presentations, instructional videos, online quizzes, and simple virtual classrooms supported by AI tools. Participants also demonstrated high enthusiasm and positive attitudes toward technology integration in education. The learning media products developed during the workshop reflected teachers’ ability to apply technology more creatively and innovatively according to instructional needs. This activity contributed positively to strengthening teachers’ digital competencies and promoting more interactive, effective, and student-centered learning. Therefore, continuous mentoring is recommended to ensure the sustainable implementation of IT-based learning media in classroom practices.